Shake Table Study on the Efficiency of Seismic Base Isolation Using Natural Stone Pebbles - Ivan Banović; Jure Radnić; Nikola Grgić (Advances in Materials Science and Engineering)
The results of a shake table study of the efficiency of a seismic base isolation using a layer of natural stone pebbles are presented. Models of stiff and medium-stiff buildings were tested. Case studies were conducted with the foundation of model on the rigid base and on four different layers of pebbles (thin and thick layer with small and large pebbles). Four different horizontal accelerograms were applied, and the characteristic displacements, accelerations, and strains were measured. Strains/stresses of the tested models remained in the elastic area. It was concluded that the effectiveness of the stone pebble layer under the foundation, i.e., the reduction in the seismic forces and stresses in the structure compared to the classical solution of foundation, significantly depends on the type of the applied excitation and depends relatively little on the layer thickness and pebble fraction. The results of the study showed that a layer of pebbles can significantly reduce the peak acceleration and strains/stresses of the model, with acceptable displacements. Further research is expected to confirm the effectiveness of this low-cost and low-tech seismic base isolation and to pave the way to its practical application.